Evolusi, Kepegarian, dan Spiritualitas: Memahami Realitas Pandemi dan Pasca-Pandemi Berdasarkan Pemikiran Ilia Delio - Stepanus Ammai Bungaran (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
This article assesses the pandemic and post-pandemic situation from a theological lens. The Covid-19 pandemic abruptly halted the order of life. Covid-19 imposes a new lifestyle that seems to persist even after the pandemic is considered to have passed. In this regard, it is no longer possible to see the pandemic as